A Prospective Randomized Study of Operative Treatment for Noncomminuted Humeral Shaft Fractures: Conventional Open Plating Versus Minimal Invasive Plate Osteosynthesis. Issue 4 (April 2015) - Kim, Ji Wan; Oh, Chang-Wug; Byun, Young-Soo; Kim, Jung Jae; Park, Ki Chul
Abstract : Objectives: To compare the clinical and radiologic results of conventional open plating (COP) and minimally invasive plate osteosynthesis (MIPO) in the treatment of noncomminuted humeral shaft fractures. Design: Randomized prospective study. Setting: Five level 1 trauma centers. Patients: Sixty-eight consecutive patients were randomized into 2 study groups: those treated by COP (COP group; n = 32) and those treated by MIPO (MIPO group; n = 36). Intervention: Simple humeral shaft fractures (AO/OTA classification types A and B) were reduced by open reduction or closed reduction and fixed with a narrow 4.5/5.0 locking compression plate, metaphyseal locking compression plate, or proximal humeral internal locking system plate to the anterior lateral aspect of the humerus. Main Outcome Measurements: Fracture healing time, operative time, radiation exposure time, and intraoperative nerve injury. To assess shoulder and elbow function, we used the University of California, Los Angeles (UCLA) scoring system and the Mayo elbow performance index, including the range of motion and pain. Radiographic measurements included fracture alignment, delayed union, and nonunion. Results: Thirty-one fractures (97%) healed in the COP group within 16 weeks, whereas 36 fractures (100%) were healed in the MIPO group by 15 weeks. No significant difference was observed in the operative time or complication rates. In both groups, all fractures achieved union without malunion and with excellent functional outcomes by definition of the Mayo elbow performance index and UCLA scoring system. Conclusions: This study confirmed a high overall rate of union and excellent functional outcomes in both MIPO and COP groups. MIPO is equivalent to COP as a safe and effective method for simple types of humeral shaft fractures when surgery is indicated, and the surgeon is experienced in the technique. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.